Diagnostic value of cardiac miR-126-5p, miR-134-5p, and miR-499a-5p in coronary artery disease-induced sudden cardiac death - Li, Linfeng; He, Xiangwang; Liu, Min; Yun, Libing; Cong, Bin (Frontiers in Cardiovascular Medicine, 2022)
Background The identification of coronary artery disease-induced sudden cardiac death (CAD-SCD) has always been a medical challenge. MicroRNAs (miRNAs) played vital roles in pathogenesis processes and served as potential biomarkers for cardiovascular and many other diseases. The aim of this study was to investigate the diagnostic value of the specific miRNAs for CAD-SCD. Methods Thirty autopsy-verified CAD-SCD victims were selected, including 18 individuals experienced more than once asymptomatic myocardial ischemia (CAD-activated SCD), and 12 victims without prominent pathological features of insufficient blood supply (CAD-silent SCD). Meanwhile, 30 traumatic victims were enrolled as controls. Systematic postmortem examinations were performed in all study population. The expressions of cardiac miR-126-5p, miR-134-5p and miR-499a-5p were analyzed by real-time quantitative polymerase chain reaction (RT-qPCR). Results RT-qPCR showed significant down‐regulations of miR-126-5p and miR-499a-5p in CAD-SCD victims, with no obvious difference in miR-134-5p. Receiver operating characteristic analysis revealed the diagnostic performance of miR-126-5p (areas under the curve (AUC) = 0.76), and validated miR-499a-5p (AUC = 0.82) as a sensitive marker. Additionally, the decreased expression of the two specific cardio‐miRNAs were detected for discriminating CAD-silent SCD and CAD-activated SCD. Compared with the limited diagnostic value of single miR-126-5p and miR-499a-5p, their combination could achieve better discriminative capacity (AUC = 0.82, sensitivity = 91.7%, specificity = 77.8%). Conclusion Cardiac miR-126-5p and miR-499a-5p presented good diagnostic abilities for CAD-SCD, and their combination could help evaluate CAD condition. These targeted miRNAs as novel biomarkers are expected to be useful to discriminate for detailed causes in real SCD cases.